Effect of sowing time on productivity of Bt and non Bt cotton under climate change - K Sankaranarayanan; A H Prakash; K Rajendran (Bulletin of the National Research Centre, 2020)
Abstract Background Climate change affects cotton production systems in multiple ways, and the impacts are expected to influence the national economy of India. The weather conditions prevailing during squaring, flowering and boll development stages determine the seed cotton yield. The needs for adaptation connected to optimizing the timing of critical growth stages to minimize stresses and enhance resource utilization. The adjusting of sowing times proved to be an important management technique for improving seed cotton yield. Results The combined results for 3 years revealed that seed cotton yield was not influenced significantly by genotypes and interaction effect. However, the effect of date of sowing was significant. The best date of sowing was on 28 July which recorded the highest significant mean seed cotton yield (24.8 q/ha) compared with other sowing dates. Conclusions Three years results of experiments show that the best date for sowing is 28 July which is optimum to realize higher productivity and profitability. Sowing window of cotton was re-standardized as from 21 July to 18 August. The existing recommendation of sowing window is 1 August to 31 August.